PSYCHOLOGY IN LITERATURE - Radjabova Dildora Rakhimovna (Zeta Repository, 2023)
The goal of this paper is to discuss literature in terms of its interdisciplinary structure, specifically psychology, which has always been studied by writers, philosophers, artists, psychologists, in terms of man and existence, personality, and individual differences. It is clear that there is a strong relationship between literature and psychology because both deal with humans and their reactions, desires, and individual and social concerns using different concepts, methods, and approaches.